2022
DOI: 10.1111/aab.12756
|View full text |Cite
|
Sign up to set email alerts
|

Soluble organic nutrients induce ClaPhys expression to enhance phytase activity of watermelon roots

Abstract: Application of organic fertilisers is beneficial to the quality and yield of crops. Myoinositol phosphate is an abundant form of organic phosphorus (P o ) in organic manure and soil, which could release phosphate (P i ) and likely be absorbed by plant after it was hydrolysed by phytase. However, whether plant roots respond to organic fertiliser to adapt myo-inositol phosphates utilisation is not clear. Experiments were carried out to investigate the responses of phytase gene expression and enzyme activity, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Phosphatases dephosphorylate organic phosphorus such as phosphomonoesters, diesters, DNA, ATP, and phosphohexose, releasing Pi for absorption into the roots (Robinson et al, 2012;Shen et al, 2011). Plant roots secrete APase to hydrolyze Po, releasing Pi into the rhizosphere (Aslam et al 2022;Li et al 2022), and it has been shown that APase activity increases under phosphate deficiency stress (Li et al 2017;Tran et al 2010). Here we found that OF application induced an increase in APase activity in rice root secretions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphatases dephosphorylate organic phosphorus such as phosphomonoesters, diesters, DNA, ATP, and phosphohexose, releasing Pi for absorption into the roots (Robinson et al, 2012;Shen et al, 2011). Plant roots secrete APase to hydrolyze Po, releasing Pi into the rhizosphere (Aslam et al 2022;Li et al 2022), and it has been shown that APase activity increases under phosphate deficiency stress (Li et al 2017;Tran et al 2010). Here we found that OF application induced an increase in APase activity in rice root secretions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Jarosch et al (2019) APase in soil promotes utilization of organic fertilizer Phosphatase is the main enzyme responsible for hydrolyzing phosphomonoesters, which are the main form of Po in OF (Shen et al 2011). After OF is applied in the field, Po dissolves and diffuses in the soil, this induces APase secretion from plant roots, which hydrolyzes Po and releases Pi in the rhizosphere (Li et al 2022). Inositol hexaphosphate, the main phosphomonoester in OF, is the substrate of APase (Liu et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass has a unique microporous structure and some functional groups that can cut off the continuity of soil capillaries, inhibit the transport and accumulation of water and salts to the upper layers of the soil ( Wu et al., 2021c ), and improve soil porosity and structure by forming iron complexes to increase soil aggregates ( Li et al., 2021 ; Chen et al., 2022 ). In addition, the exogenous application of biomass increases the content of energy substrates and bioactive substances in soil ( Kaur et al., 2005 ; Wong et al., 2009 ), significantly increases soil microbial and enzyme activities, and regulates soil microbial community structure ( Wu et al., 2021a ), thus favorably affecting plant root and aboveground growth and soil ecology ( Chen et al., 2021b ; Li et al., 2022a ). However, the differences in composition and internal mechanism among biomass materials lead to their varying effects on the growth of salt-tolerant forage grasses in saline–alkaline soil and the improvement of the soil itself ( Amini et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%